Signal‐Amplified Analysis of Molecular Layers Prepared through Bipolar Electrochemistry. Issue 3 (28th September 2015) - Shida, Naoki; Kitamura, Fusao; Fuchigami, Toshio; Tomita, Ikuyoshi; Inagi, Shinsuke
Abstract: In this article, we investigate the surface modification of an indium tin oxide (ITO) plate as a bipolar electrode (BPE) by bipolar electrolysis with the well‐established electrochemistry of aryl diazonium salts. To study in detail the formation behavior of a molecular layer of the aryl groups, we employ two different approaches, namely, the direct analysis of the layer and the indirect analysis based on the idea of signal amplification by the surface‐initiated polymerization (SIP) technique. For the direct analysis, we made X‐ray photoelectron spectroscopy (XPS) measurements of the molecular layer and find that the amount of the aryl group introduced is in a gradient manner, reflecting the potential slope generated on the BPE. After the SIP process, signals amplified by the grafting polymers can be detected by infrared reflection absorption spectroscopy (IR–RAS) and film thickness measurement with a stylus‐type tester. Atomic force microscopy (AFM) measurement of the surface of the polymer brush was also carried out. These indirect methods afford detailed information on the modification behavior of the original molecular layer prepared through the bipolar electrolysis process. Abstract : Loud and clear : The surface modification of an indium tin oxide plate as a bipolar electrode with the reduction of aryl diazonium salts is investigated. The direct analysis of the molecular layer by XPS and the indirect analysis by IR–RAS, film thickness, and AFM measurements after signal amplification by the surface‐initiated polymerization technique are demonstrated.